Transições de fase dinâmicas, parâmetros de ordem conservados e não conservados e a transição de desconﬁnamento na QCD - Pereira, Aline Olimpio [UNESP] (2009)
We study the time evolution of conserved and nonconserved order parameters employing the formalism of the semiphenomenological Ginzburg-Landau-Langevin kinetic equations of the classical theory of dynamical phase transitions. We present an application of the formalism to the deconfinement problem of quarks and gluons in QCD, where the conserved order parameter is the baryon density and the non-conserved order parameter is the Polyakov loop. The kinetic equations are solved numerically employing a semi-implicit scheme for the time variable and a finite-difference method with fast Fourier transform for the space coordinates. Results of the numerical simulations are presented for the average values and structure functions of the order parameters